Method for evaluating long-term storage performance of fiber reinforced resin-based composite material

By combining instrument analysis and single-temperature and humidity point accelerated aging test, the long-term storage performance of fiber-reinforced resin-based composite materials was evaluated, and the problem of not considering the influence of humidity and the time-consuming time of multi-temperature point tests in the prior art was solved, and a rapid and efficient performance evaluation was achieved.

CN119715330AActive Publication Date: 2025-03-28SHANDONG NON METALLIC MATERIAL RESEARCH INSTITUTE
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411609141.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-03-28
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The prior art does not consider the influence of humidity when evaluating the long-term storage properties of fiber-reinforced resin-based composites, and requires accelerated aging tests at multiple temperature points, which consumes a lot of manpower and material resources and has a long test time.

Method used

Using a combination of instrument analysis and single temperature and humidity point accelerated aging test, the temperature and humidity of accelerated aging are designed, the apparent activation energy of thermal weight loss of the material is measured, the acceleration coefficient is calculated, and the constant temperature and humidity accelerated aging test is carried out. Samples are taken according to the cycle and the material performance is measured, and the evaluation model is established through regression analysis.

Benefits of technology

Rapidly evaluate the long-term storage performance of fiber-reinforced resin-based composites, and shortened the test cycle to 1 to 3 months, improving the evaluation efficiency and saving manpower and material resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The invention discloses a method for evaluating the long-term storage performance of a fiber-reinforced resin-based composite material, and belongs to the technical field of fiber-reinforced resin-based composite materials. The thermal weight loss apparent activation energy of the fiber reinforced resin matrix composite material is measured through an instrument analysis method, the activation energy is subjected to coefficient calculation and then serves as the aging activation energy of the material, the acceleration coefficient is calculated according to the aging activation energy, the accelerated aging test temperature and the storage temperature, and then the accelerated aging time is obtained. The method comprises the following steps: carrying out a constant temperature and humidity accelerated aging test, determining the performance of the aged material, carrying out regression analysis on obtained test data, establishing a regression equation, and evaluating the performance of the composite material in corresponding natural storage time by using a calculated value of the regression equation. And manpower and material resources are saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fiber-reinforced resin-based composite materials, and in particular relates to a method for evaluating the long-term storage performance of fiber-reinforced resin-based composite materials. Background Art

[0002] During long-term storage, fiber-reinforced resin-based composite materials will age under the influence of heat, oxygen and moisture, resulting in their macroscopic properties being unable to meet the requirements of use. Premature damage to composite materials will cause waste of resources and may also lead to larger accidents. Therefore, the long-term storage performance evaluation of fiber-reinforced resin-based composite materials has always been a hot topic of concern.

[0003] In terms of long-term storage performance and life assessment methods for polymer materials, the methods currently commonly used include ISO 2578:1993, ISO 11346:2014, GB / T 20028-2005, GB / T 7142-2002, GJB-92.1-86, GJB-92.2-86 and HG / T 3087-2001. Among them, ISO 2578:1993, ISO 11346:2014, GB / T 20028-2005 and GB / T 7142-2002 are similar. GB / T 7142-2002 is equivalent to ISO 2578:1993, and GB / T 20028-2005 is equivalent to ISO 11346:1997. The main contents of these methods are to carry out accelerated aging tests under no less than 3 temperature conditions, and obtain the failure time under each temperature condition. Then, data processing is performed according to the Arrhenius law to evaluate the storage life of the material. The three methods of GJB-92.1-86, GJB-92.2-86 and HG / T 3087-2001 are similar in content. Accelerated aging tests are carried out under no less than 4 temperature conditions. The data processing method is to first perform linear regression on the logarithm of the performance retention rate-time (lnp-tα) to obtain the rate change constant K and other constants at different accelerated temperatures. Then, according to the Arrhenius law, the logarithm of the rate change constant-the inverse of the test temperature (lnK-1 / T) is linearly regressed to obtain the rate change constant at the storage temperature, thereby establishing a performance degradation model to evaluate the storage life of the material. Among the above methods, GB / T 7142-2002 and ISO 2578:1993 are applicable to the life assessment of plastic materials, and fiber-reinforced resin-based composite materials can be used as a reference.

[0004] The above methods do not take into account the influence of humidity on materials. When used for the long-term storage performance evaluation of fiber-reinforced resin-based composite materials, it may lead to a large deviation between the evaluation results and the actual test results. Moreover, the above methods all require accelerated aging tests at multiple temperature points, which not only requires a lot of manpower and material resources, but also takes a long time to test. Therefore, in actual operation, it is often difficult for the tester to bear. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for evaluating the long-term storage performance of fiber-reinforced resin-based composite materials. The method combines instrumental analysis and single temperature and humidity point accelerated aging tests to quickly evaluate the long-term storage performance of fiber-reinforced resin-based composite materials. The test period is usually 1 to 3 months, which is significantly shorter than the test period of existing evaluation methods.

[0006] In order to solve the above technical problems, the present invention adopts the following technical scheme: first, the temperature and humidity for accelerated aging are designed, and the thermal weight loss apparent activation energy of the fiber-reinforced resin-based composite material is measured, and the coefficient of this activation energy is calculated as the aging activation energy of the composite material; then, the acceleration coefficient is calculated according to the aging reaction activation energy, the accelerated aging test temperature and the storage temperature, and the required accelerated aging time is calculated according to the obtained acceleration coefficient and the expected storage time, and a constant temperature and humidity accelerated aging test is carried out, and material properties are sampled and measured according to the period; finally, regression analysis is performed on the obtained test data, a regression equation is established, and the calculated value of the regression equation is used to evaluate the performance of the composite material at the corresponding natural storage time.

[0007] The method for evaluating the long-term storage performance of a fiber-reinforced resin-based composite material according to the present invention comprises the following steps: (1) Design of accelerated aging test conditions The test temperature is not higher than 75°C and the test humidity is 65g / m 3 ; (2) Determine the activation energy of the aging reaction of fiber-reinforced resin-based composites According to the method provided by ASTM E1641, the apparent activation energy of the fiber-reinforced resin matrix composite material when the resin-air atmosphere thermal weight loss rate is 5% is determined; the coefficient of this thermal weight loss apparent activation energy is calculated as the aging reaction activation energy of the fiber-reinforced resin matrix composite material E a ; (3) Conduct accelerated aging tests on fiber-reinforced resin-based composite materials and test the material properties after the tests Calculate the acceleration factor based on the accelerated aging test temperature and aging reaction activation energy obtained in steps (1) and (2) and the expected storage temperature; then calculate the accelerated aging test time based on the obtained acceleration factor and the expected storage time; round the calculated result of the accelerated aging test time to an integer, carry out a constant temperature and humidity accelerated aging test, and regularly take samples and test the material properties after aging; (4) Fitting the regression equation of the change of fiber reinforced resin matrix composite performance with accelerated aging time A polynomial regression analysis was performed with the accelerated aging test time as the independent variable and the performance test value of the fiber-reinforced resin-based composite material as the dependent variable, and the regression equation of the fiber-reinforced resin-based composite material performance changing with the accelerated aging time was obtained. (5) Evaluating the performance of fiber-reinforced resin-based composites with required storage time Using the regression equation obtained in step (4), the performance of the fiber-reinforced resin-based composite material at the required storage time is evaluated.

[0008] Preferably, the test temperature of the accelerated aging test in step (1) is 75°C.

[0009] Preferably, in step (2), when calculating the apparent activation energy of thermal weight loss, the coefficient taken is 0.6-0.7.

[0010] Preferably, when calculating the acceleration coefficient in step (3), the Arrhenius equation is used:

[0011] Where: F — acceleration factor; k 1 —Aging rate constant at storage temperature; k 2 —Aging rate constant under accelerated aging conditions; E a —Activation energy of aging reaction, J·mol-1; R —Gas constant, 8.314 J·K-1·mol-1; T 1 —Storage temperature, K; T 2 —Accelerated aging test temperature, K.

[0012] Preferably, the accelerated aging test time is calculated in step (3) according to the obtained acceleration factor and the expected storage time, using the following formula:

[0013] Where: t 2 —Accelerated aging test time, d;t 1 —Expected storage time, d.

[0014] Preferably, the step (3) tests the material properties of the fiber-reinforced resin-based composite material after accelerated aging test, including flexural strength and flexural modulus.

[0015] The present invention relates to a method for evaluating the long-term storage performance of fiber-reinforced resin-based composite materials. The method adopts a method combining instrumental analysis and single temperature and humidity point accelerated aging tests to evaluate the long-term storage performance of fiber-reinforced resin-based composite materials. Compared with existing methods, the test time can be shortened, the efficiency can be improved, and manpower and material resources can be saved. DETAILED DESCRIPTION

[0016] The present invention is further described below in conjunction with specific embodiments, but is not intended to limit the technical solutions of the present invention.

[0017] Embodiment 1 Taking the long-term storage performance evaluation of carbon fiber reinforced phenolic resin-based composite materials as an example, this paper introduces the material bending strength evaluation method of the composite material stored at room temperature 23°C for 10 years. The specific evaluation steps are as follows: (1) The accelerated aging test temperature is designed to be 75°C and the test humidity is 65g / m 3 .

[0018] (2) The material was subjected to air atmosphere thermal gravimetric analysis at different heating rates, namely 1°C, 2°C, 5°C and 10°C. According to the method provided by ASTM E1641, when the thermal weight loss rate of the resin in the composite material was 5%, the corresponding thermal weight loss apparent activation energy was calculated to be 1.155×10 5 J / mol, the apparent activation energy of thermal weight loss is calculated as 0.65, which is the activation energy of the aging reaction of carbon fiber reinforced phenolic resin composite material. E a , is 7.508×10 4 J / mol.

[0019] (3) Carry out aging tests on fiber-reinforced resin-based composite materials and test the material properties after aging Calculate the acceleration factor according to formula (1): (1) Where: F — acceleration factor; k 1 —Aging rate constant at storage temperature; k 2 —Aging rate constant under accelerated aging conditions; E a—Activation energy of aging reaction, J·mol -1 ; R —Gas constant, 8.314 J·K -1 ·mol -1 ; T 1 —Storage temperature, K; T 2 —Accelerated aging test temperature, K; t 2 —Accelerated aging test time, d; t 1 —Expected storage time, d.

[0020] Calculate the required accelerated aging test time according to formula (2): (2) The calculated result of the accelerated aging test time is rounded up to 39 days.

[0021] The accelerated aging test temperature was 75°C and the test humidity was 65 g / m 3 In an environment of 39 days, a 39-day accelerated aging test was carried out on the carbon fiber reinforced phenolic resin matrix composite material. The flexural strength of the composite material was measured after each sampling. The test results are shown in Table 1.

[0022] Table 1 Bending strength test results

[0023] (4) A polynomial regression analysis was performed with the accelerated aging test time as the independent variable and the flexural strength test value of the carbon fiber reinforced phenolic resin-based composite material as the dependent variable to obtain the regression equation for the change of the flexural strength of the composite material with the accelerated aging time, as shown in formula (3).

[0024] (3) Where: y 1 —Flexural strength, MPa; x-test time, d.

[0025] (5) When evaluating the flexural strength of carbon fiber reinforced phenolic resin-based composite materials stored for 8 years, the corresponding accelerated aging time calculated using formula (2) is 30.7 days. Substituting this time into formula (3), the flexural strength evaluation value of the material after 8 years of storage is calculated to be 146 MPa.

[0026] The present invention adopts a method combining instrumental analysis with accelerated aging tests at a single temperature and humidity point, and can complete the flexural strength evaluation of fiber-reinforced resin-based composite materials after long-term storage in a relatively short time, with high efficiency and saving manpower and material resources.

[0027] Embodiment 2 Taking the long-term storage performance evaluation of glass fiber reinforced epoxy resin-based composite materials as an example, this paper introduces the flexural strength evaluation method of the composite materials stored at room temperature 23°C for 10 years. The specific evaluation steps are as follows: (1) The accelerated aging test temperature is designed to be 75°C and the test humidity is 65g / m 3 .

[0028] (2) The material was subjected to air atmosphere thermal gravimetric analysis at different heating rates, namely 1°C, 2°C, 5°C and 10°C. According to the method provided by ASTM E1641, when the weight loss rate of the resin in the composite material was 5%, the corresponding thermal gravimetric apparent activation energy was calculated to be 1.285×10 5 J / mol, the apparent activation energy of thermal weight loss is calculated as the activation energy of the aging reaction of glass fiber reinforced epoxy resin composite material by taking the coefficient of 0.6 E a , is 7.71×10 4 J / mol.

[0029] (3) Calculate the acceleration factor according to formula (1):

[0030] Where: F — acceleration factor; k 1 —Aging rate constant at storage temperature; k 2 —Aging rate constant under accelerated aging conditions; E a —Activation energy of aging reaction, J·mol -1 ; R —Gas constant, 8.314 J·K -1 ·mol -1 ; T 1 —Storage temperature, K; T 2 —Accelerated aging test temperature, K; t 2 —Accelerated aging test time, d; t 1 —Expected storage time, d. Calculate the required accelerated aging test time according to formula (2):

[0031] The accelerated aging test temperature was 75°C and the test humidity was 65 g / m 3 In an environment of 34 days, a 34-day accelerated aging test was carried out on the glass fiber reinforced epoxy resin matrix composite material. The flexural strength of the composite material was measured after each sampling. The test results are shown in Table 2.

[0032] Table 2 Bending strength test results

[0033] (4) A polynomial regression analysis was performed with the accelerated aging test time as the independent variable and the flexural strength test value of the glass fiber reinforced epoxy resin matrix composite material as the dependent variable to obtain the regression equation of the flexural strength of the composite material changing with the accelerated aging time, as shown in formula (4).

[0034] (4) Where: y 2 —Flexural strength, MPa; x-test time, d.

[0035] (5) When evaluating the flexural strength of the glass fiber reinforced epoxy resin-based composite material stored for 8 years, the corresponding accelerated aging time is calculated as 27.2 days using formula (2). Substituting this time into formula (4), the estimated flexural strength of the material after 8 years of storage is calculated to be 299 MPa.

[0036] The present invention adopts a method combining instrumental analysis with accelerated aging tests at a single temperature and humidity point, and can complete the flexural strength evaluation of fiber-reinforced resin-based composite materials after long-term storage in a relatively short time, with high efficiency and saving manpower and material resources.

[0037] Embodiment 3 Taking the long-term storage performance evaluation of carbon fiber reinforced phenolic resin-based composite materials as an example, this paper introduces the material bending modulus evaluation method of the composite material stored at room temperature 23°C for 10 years. The specific evaluation steps are as follows: (1) The accelerated aging test temperature is designed to be 70°C and the test humidity is 65g / m 3 .

[0038] (2) The material was subjected to air atmosphere thermal gravimetric analysis at different heating rates, namely 1°C, 2°C, 5°C and 10°C. According to the method provided by ASTM E1641, when the weight loss rate of the resin in the composite material was 5%, the corresponding thermal gravimetric apparent activation energy was calculated to be 1.155×10 5 J / mol, the apparent activation energy of thermal weight loss is calculated as 0.7, which is the activation energy of the aging reaction of carbon fiber reinforced phenolic resin composite material. E a , is 8.085×10 4 J / mol.

[0039] (3) Calculate the acceleration factor according to formula (1):

[0040] Where: F — acceleration factor; k 1 —Aging rate constant at storage temperature; k 2 —Aging rate constant under accelerated aging conditions; E a —Activation energy of aging reaction, J·mol -1 ; R —Gas constant, 8.314 J·K -1 ·mol -1 ; T 1 —Storage temperature, K; T 2 —Accelerated aging test temperature, K; t 2 —Accelerated aging test time, d; t 1 —Expected storage time, d. Calculate the required accelerated aging test time according to formula (2):

[0041] The calculated result of the accelerated aging test time is rounded up to 41 days.

[0042] The accelerated aging test temperature was 70°C and the test humidity was 65 g / m 3 In an environment of , a 41-day accelerated aging test was carried out on the carbon fiber reinforced phenolic resin matrix composite material. The flexural modulus of the composite material was measured after each sampling. The test results are shown in Table 3.

[0043] Table 3 Flexural modulus test results

[0044] (4) A polynomial regression analysis was performed with the accelerated aging test time as the independent variable and the flexural modulus test value of the carbon fiber reinforced phenolic resin-based composite material as the dependent variable to obtain the regression equation for the change of the flexural modulus of the composite material with the accelerated aging time, as shown in formula (5).

[0045] (5) Where: y 3 —Flexural modulus, GPa; x-test time, d.

[0046] (5) When evaluating the flexural modulus of the carbon fiber reinforced phenolic resin-based composite material stored for 9 years, the corresponding accelerated aging time is calculated as 36.6 d using formula (2). Substituting this time into formula (5), the flexural modulus evaluation value of the material after 9 years of storage is calculated to be 21.7 GPa.

[0047] The present invention adopts a method combining instrumental analysis with accelerated aging tests at a single temperature and humidity point, and can complete the evaluation of the flexural modulus of fiber-reinforced resin-based composite materials after long-term storage in a relatively short time, with high efficiency and saving manpower and material resources.

Claims

1. A method for evaluating the long-term storage performance of a fiber-reinforced resin-based composite material, characterized in that: The steps of this method are: (1) Design of accelerated aging test conditions The test temperature is not higher than 75°C and the test humidity is 65g / m 3 ; (2) Determine the activation energy of the aging reaction of fiber-reinforced resin-based composites According to the method provided by ASTM E1641, the apparent activation energy of the fiber-reinforced resin matrix composite material when the resin-air atmosphere thermal weight loss rate is 5% is determined; the coefficient of this thermal weight loss apparent activation energy is calculated as the aging reaction activation energy of the fiber-reinforced resin matrix composite material E a ; (3) Conduct accelerated aging tests on fiber-reinforced resin-based composite materials and test the material properties after the tests Calculate the acceleration factor based on the accelerated aging test temperature and aging reaction activation energy obtained in steps (1) and (2) and the expected storage temperature; then calculate the accelerated aging test time based on the obtained acceleration factor and the expected storage time; The calculated result of the accelerated aging test time is rounded up to an integer, and the accelerated aging test under constant temperature and humidity is carried out. Samples are taken regularly and the performance of the materials after aging is tested. (4) Fitting the regression equation of the change of fiber reinforced resin matrix composite performance with accelerated aging time A polynomial regression analysis was performed with the accelerated aging test time as the independent variable and the performance test value of the fiber-reinforced resin-based composite material as the dependent variable, and the regression equation of the fiber-reinforced resin-based composite material performance changing with the accelerated aging time was obtained. (5) Evaluating the performance of fiber-reinforced resin-based composites with required storage time Using the regression equation obtained in step (4), the performance of the fiber-reinforced resin-based composite material at the required storage time is evaluated.

2. The method for evaluating the long-term storage performance of a fiber-reinforced resin-based composite material according to claim 1, characterized in that: The test temperature of the accelerated aging test in step (1) is 75°C.

3. The method for evaluating the long-term storage performance of a fiber-reinforced resin-based composite material according to claim 1, characterized in that: In the step (2), when calculating the apparent activation energy of thermal weight loss, the coefficient taken is 0.6-0.

7.

4. The method for evaluating the long-term storage performance of a fiber-reinforced resin-based composite material according to claim 1, characterized in that: When calculating the acceleration factor in step (3), the Arrhenius equation is used: Where: F — acceleration factor; k 1—Aging rate constant at storage temperature; k 2—Aging rate constant under accelerated aging conditions; E a —Activation energy of aging reaction, J·mol -1 ; R —Gas constant, 8.314 J·K -1 ·mol -1 ; T 1—Storage temperature, K; T 2—Accelerated aging test temperature, K.

5. The method for evaluating the long-term storage performance of a fiber-reinforced resin-based composite material according to claim 1, characterized in that: In step (3), the accelerated aging test time is calculated based on the obtained acceleration factor and the expected storage time, using the following formula: Where: t 2—Accelerated aging test time, d; t 1—Expected storage time, d.

6. The method for evaluating the long-term storage performance of a fiber-reinforced resin-based composite material according to claim 1, characterized in that: The step (3) tests the material properties of the fiber-reinforced resin-based composite material after the accelerated aging test, including the flexural strength and flexural modulus.

Citation Information

Patent Citations

  • Polymer material thermal ageing life assessment method based on variable activation energy

    CN109030548A

  • Explosion suppression material accelerated aging test design and service life estimation method

    CN115206461A

  • Method for predicting service life of polyaryletherketone resin-based thermoplastic composite material

    CN115541480A

  • Accelerated life evaluation method for in-vivo implanted wire

    CN116741325A

  • Method and system for testing aging performance of marine cable

    CN117782957A